Role of Bio-filtration in Petrochemical Wastewater Treatment using CSTR - Siddique, Md. Nurul Islam; Zularisam, A. W. (Penerbit Universiti Malaysia Pahang, 2014)
Continuous stirred tank reactors (CSTR)operated at 35"C, were efficaciously used for the anaerobic digestion of a petrochemical effluent. Biofiltrationof petrochemical wastewater was carried out and the results were evaluated in terms of basic water quality parameters. The effects of organic loadings, solid retention time were also investigated. COD reductions of 93-98% were found at an optimum retention time of 2.3 days and a loading rate of 4.7 kg COD/m3/d. The amount of biogas produced was 0.88 m3/m3/d (STP) with a methane content of 90-96%. Volatile fatty acid removal was also achieved up to 97% after performing biofiltration process. Therefore, the current work revils that bio-filtration of petrochemical wastewater using CSTR might be an effective solution to the prevailing treatment limitation.